DAMPAK PEMBELAJARAN DARING SELAMA PANDEMI COVID-19 BAGI SISWA SEKOLAH DASA - Eny Yulia Susanti (EJoES (Educational Journal of Elementary School), 2020)
This study aims to describe the impact of online learning during the Covid-19 pandemic for elementary school students. This type of research is library research using data sources from books, journals and internet sites related to the selected topic. The results showed that online learning can help learning activities as long as students learn from home. Apart from the advantages that online learning has, various challenges are also found by teachers and students in learning. A common problem relates to the signals and learning devices used in online learning.